Спрости вираз - (b+2)*(a-5)-(c-b) та знайди його значення, якщо а=26;b=-3,47;c=19

Нуртилек2664467 Нуртилек2664467    1   15.02.2022 07:54    0

Ответы
Ayshalike Ayshalike  15.02.2022 08:00

8,4

Пошаговое объяснение:

-(b+2)*(a-5)-(c-b) при а = 26; b = -3,47; с = 19

-(b+2)*(a-5)-(c-b) = -ab - 2a + 5b + 10 - c + 2b = -ab - 2a + 6b - c + 10

-ab - 2a + 6b - c + 10 = -26*(-3,47) - 2*26 + 6*(-3,47) - 19 + 10 =

90,22 - 52 - 20,82 - 9 = 90,22 - 81,82 = 8,4

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика